Etiologies, clinical features and outcome of cardiac arrest in HIV-infected patients. (15th December 2015) - Mongardon, Nicolas; Geri, Guillaume; Deye, Nicolas; Sonneville, Romain; Boissier, Florence; Perbet, Sébastien; Camous, Laurent; Lemiale, Virginie; Thirion, Marina; Mathonnet, Armelle; Argaud, Laurent; Bodson, Laurent; et al.
Abstract: Background: Compared to many other cardiovascular diseases, there is a paucity of data on the characteristics of successfully resuscitated cardiac arrest (CA) patients with human immunodeficiency virus (HIV) infection. We investigated causes, clinical features and outcome of these patients, and assessed the specific burden of HIV on outcome. Methods: Retrospective analysis of HIV-infected patients admitted to 20 French ICUs for successfully resuscitated CA (2000–2012). Characteristics and outcome of HIV-infected patients were compared to those of a large cohort of HIV-uninfected patients admitted after CA in the Cochin Hospital ICU during the same period. Results: 99 patients were included (median CD4 lymphocyte count 233/mm 3, viral load 43 copies/ml). When compared with the control cohort of 1701 patients, HIV-infected patients were younger, with a predominance of male, a majority of in-hospital CA (52%), and non-shockable initial rhythm (80.8%). CA was mostly related to respiratory cause (n = 36, including 23 pneumonia), cardiac cause (n = 33, including 16 acute myocardial infarction), neurologic cause (n = 8) and toxic cause (n = 5). CA was deemed directly related to HIV infection in 18 cases. Seventy-one patients died in the ICU, mostly for care withdrawal after post-anoxic encephalopathy. After propensity score matching, ICU mortality was not significantly affected by HIV infection. Similarly, HIV disease characteristics had no impact on ICU outcome. Conclusions: Etiologies of CA in HIV-infected patients are miscellaneous and mostly not related to HIV infection. Outcome remains bleak but is similar to outcome of HIV-negative patients.